High-Performance Photoresistors Based on Perovskite Thin Film with a High PbI2 Doping Level - Jieni Li; Henan Li; Dong Ding; Zibo Li; Fuming Chen; Ye Wang; Shiwei Liu; Huizhen Yao; Lai Liu; Yumeng Shi (Nanomaterials, 2019)
We prepared high-performance photoresistors based on CH3NH3PbI3 films with a high PbI2 doping level. The role of PbI2 in CH3NH3PbI3 perovskite thin film was systematically investigated using scanning electron microscopy, X-ray diffraction, time-resolved photoluminescence spectroscopy, and photoconductive atomic force microscope. Laterally-structured photodetectors have been fabricated based on CH3NH3PbI3 perovskite thin films deposited using precursor solution with various CH3NH3I:PbI2 ratios. Remarkably, the introduction of a suitable amount of PbI2 can significantly improve the performance and stability of perovskite-based photoresistors, optoelectronic devices with ultrahigh photo-sensitivity, high current on/off ratio, fast photo response speed, and retarded decay. Specifically, a highest responsivity of 7.8 A/W and a specific detectivity of 2.1 × 1013 Jones with a rise time of 0.86 ms and a decay time of 1.5 ms have been achieved. In addition, the local dependence of photocurrent generation in perovskite thin films was revealed by photoconductive atomic force microscopy, which provides direct evidence that the presence of PbI2 can effectively passivate the grain boundaries of CH3NH3PbI3 and assist the photocurrent transport more effectively.